2009
DOI: 10.4028/www.scientific.net/msf.615-617.765
|View full text |Cite
|
Sign up to set email alerts
|

High Channel Mobility of 4H-SiC MOSFETs Fabricated by Over-Oxidation of the N-/Al-Coimplanted Surface Layer

Abstract: Conventional MOSFETs and Hall-bar MOSFETs are fabricated side by side by over-oxidation of N-implanted or N-/Al-coimplanted 4H-SiC layers. It is demonstrated that the N-/Al-coimplanted MOSFETs possess a positive threshold voltage at room temperature and reach high values of the channel mobility. The effective electron mobility and Hall mobility in Hall-bar MOSFETs are 31 cm2/Vs and 150 cm2/Vs, respectively, indicating a high density of interface traps in spite of the excellent high mobility values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Thus, there is a possibility that other elements can reduce D it . One good method to incorporate various elements into the SiO 2 /SiC interface is over-oxidation of ion-implanted substrates [8][9][10][11][12]. Over-oxidation of N-implanted 4H-SiC substrates significantly reduces D it near the conduction band edge [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, there is a possibility that other elements can reduce D it . One good method to incorporate various elements into the SiO 2 /SiC interface is over-oxidation of ion-implanted substrates [8][9][10][11][12]. Over-oxidation of N-implanted 4H-SiC substrates significantly reduces D it near the conduction band edge [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…One good method to incorporate various elements into the SiO 2 /SiC interface is over-oxidation of ion-implanted substrates [8][9][10][11][12]. Over-oxidation of N-implanted 4H-SiC substrates significantly reduces D it near the conduction band edge [8][9][10][11][12]. It has been reported that both flat-band voltage and D it increase by the N/Al co-implantation technique [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process also generates a large negative shift of the flatband voltage due to a positive fixed charge; this charge can be compensated by Al implantation. It has been demonstrated that N-/Al-coimplanted and over-oxidized MOSFETs possess a positive threshold voltage and a high effective mobility [4]. In this paper, the authors have studied the effect of an additional preannealing step before the over-oxidation on the electrical properties of MOSFETs.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we study as-grown as well as electron-irradiated or He + -implanted, Al-doped 4H-SiC samples predominantly by admittance spectroscopy (AS) in order to monitor energetically shallow defects. A detailed deep level transient spectroscopy (DLTS) analysis on energetically deep defects in e-irradiated p-type 4H-SiC is presented in a separate paper [6].…”
Section: Introductionmentioning
confidence: 99%